Molecular key to understand the gastric cancer biology in elderly patients—The role of microsatellite instability. Issue 3 (18th November 2016) - Polom, Karol; Marrelli, Daniele; Roviello, Giandomenico; Pascale, Valeria; Voglino, Costantino; Rho, Henry; Marini, Mario; Macchiarelli, Raffaele; Roviello, Franco
Abstract : Background and Objectives: Microsatellite instability (MSI) in gastric cancer (GC) is associated with older age. We present the clinicopathological results of younger and older patients with MSI GC. Methods: We analyzed 472 patients with GC. MSI analysis was done on fresh frozen tissue using five quasimonomorphic mononucleotide repeats: NR‐21, NR‐24, NR‐27, BAT‐25, and BAR‐26. Clinical and pathological analysis was performed for different age groups. Results: We observed better survival in elderly MSI GC patients compared to younger patients. The percentage of MSI GC increases gradually with increasing age, accounting for 48% of patients over the age of 85 years. A difference in survival was seen between MSI and MSS groups of patients older than 65 years, while no statistical difference was seen for younger groups. Multivariate analysis revealed that MSI status has a significant prognostic factor in patients aged over 70 years (MSS vs. MSI; HR 1.82, P  = 0.013). Conclusion: MSI is an important prognostic factor above all in elderly GC patients. It is associated with favorable prognosis and may help in planning different approaches to treatment in this subgroup. J. Surg. Oncol. 2017;115:344–350 . © 2016 Wiley Periodicals, Inc.